Fibrinolytic Effect of Incubating Human Blood Clots in Cinnamon Cassia Using Dose Dependent: In Vitro Assays - Elnager, Abuzar; Ahmed, Mohammed Seed (مركز بحوث ودراسات دول حوض البحر الأحمر, 2022)
الطب بالأعشاب هو استخدام النباتات الطبية للوقاية والعلاج ضد الأمراض في كل بلد فإنه يمتد من الطب التقليدي والشعبي لاستخدام مستخلصات عشبية موحدة ومموهة. الطب بالأعشاب هذه الأيام هو واحد من الطرق الشائعة لعلاج العديد من الأمراض لفعاليته وقلة آثاره الجانبية. هذه الدراسة مقارنة تجريبية أجريت في منطقة ولاية البحر الأحمر- بورتسودان تهدف إلى قياس نشاط تكسر الفبرين بواسطة مستخلص القرفة بتراكيز مختلفة في المعمل. تم تحضير جلطات دموية بشرية موحدة في تراكيز مختلفة من محلول مستخلص القرفة (0.5،1،2،4،8 و 16) %جرام/ مل بعد 0 و 3 ساعات حضانة، تم قياس مستويات ال دي دايمر ووزن جلطة الدم لكل تركيز باستخدام Ichroma والميزان الحساس. يتم تحليل البيانات بواسطة برنامج التحليل الإحصائي. وبصفة عامة كان متوسط مستويات ال دي دايمر (نغ/مل) مختلفا بشكل كبير عبر العينات التي تم تحضينها مع عدة تراكيز مختلفة من مستخلص القرفة، وكان متوسط وزن جلطة الدم (جرام) ما قبل وبعد التحضير كان هنالك فارق في الوزن. وخلصت هذه الدراسة إلى أن مستخلص القرفة بتراكيزه المختلفة يمتلك نشاط لتكسر الجلطة بعد الحضانة في المختبر، لذلك ينبغي إجراء مزيد من الاختبارات في مستخلص القرفة ليصبح واحدا من المواد البديلة المكسرة للفبرين. Introduction: Herbal medicine is the use of medicinal plants for prevention and treatment of diseases; it has less side effects and they have great effectiveness. This is an experimental comparative study was conducted in Port-Sudan city. Aim: this study to determine fibrinolytic activity of Cinnamon Cassia aqueous extract at different concentrations in vitro. Method: Standardized human whole blood clots were incubated at different concentrations of Cinnamon Cassia (0. 5, 2, 4, 8, and 16).% The D-dimer (DD) levels and WB clot weight were measured for each concentration after 3 hours of incubation using I chroma II analyzer and sensitive balance. The data was analyzed by SPSS software using one way ANOVA analysis. Results: The Overall, mean DD (ng/ml) levels were significantly different across samples incubated with Cinnamon Cassia aqueous extract at different concentrations , and the mean pre and post incubation WB clot weights (grams) were significantly decreased. Conclusion: This study concluded that Cinnamon Cassia aqueous extract possesses fibrinolytic activity following in vitro incubation of WB clot at different concentrations. Therefore, further investigations for Cinnamon Cassia aqueous extract as a potential alternative fibrinolytict agent is needed.
Keywords: النباتات الطبية -- الطب الشعبي -- جلطات الدم -- التداوي بالأعشاب